2019
DOI: 10.25301/jpda.281.33
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Postoperative Sensitivity and Composite Restorations – A Review

Abstract: The number of composite restorations delivered to patients is on the rise. Despite the improvement in mechanical properties of modern composites, the task of providing a functional restoration is at times compromised due to the problem of postoperative sensitivity associated with these restorations. An understanding of the potential causes of postoperative sensitivity will enable clinicians to adopt a technique which minimizes the risk of development of postoperative sensitivity and subsequently ensure restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Table (1): the results of the tested groups In all the tested groups 1 day gave a significant difference than one week (P= 0.011*), when comparing the control group to the gluma group, t-test gave a significant difference (0.0003*) after one day, postoperatively, and when comparing the control group to the SAD group there was also significant difference (0.01*) by using t-test (P ≤ 0.05), but when comparing all the tested groups after one week and one month by using One-Way ANOVA test, there was no significant difference (P-value= 0.36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table (1): the results of the tested groups In all the tested groups 1 day gave a significant difference than one week (P= 0.011*), when comparing the control group to the gluma group, t-test gave a significant difference (0.0003*) after one day, postoperatively, and when comparing the control group to the SAD group there was also significant difference (0.01*) by using t-test (P ≤ 0.05), but when comparing all the tested groups after one week and one month by using One-Way ANOVA test, there was no significant difference (P-value= 0.36).…”
Section: Resultsmentioning
confidence: 99%
“…The dentistry field has noticeable advances in the last few decades as well as advances in restorative dentistry, especially in bonding systems and restorative materials (1) . The recent bonding systems can achieve bonding to enamel and dentin effectively, but post-operative hypersensitivity remains a major concern for dentists after the placement of composite restorations.…”
Section: Introductionmentioning
confidence: 99%
“…11 Applying etchant in deep cavity as a component of the etch and rinse approach removed the smear layer and increased the permeability of dentin make the tooth vulnerable to postoperative sensitivity if dentinal tubules were not occluded by hybridization. 12 Amin et al conducted a similar study over a period of one week and concluded post-operative sensitivity with both self-etch adhesive and total etch adhesive remains till one week. 1 Manchorova-Veleva et al concluded in six months follow up study that there was no significant difference in the frequencies of postoperative sensitivity between self-etch and total etches adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this consideration, we chose in this study to evaluate the dentinal marginal sealing given the reduced sealing quality compared to that of enamel. However, Bhatti et al [37,38] concluded that none of the adhesive strategies are able to eliminate microleakage gaps at the cervical margins. Tjaderhane et al [19] reported that regardless of the used adhesive strategy, the portions of collagen that do not bond to the resin become prone to degradation and the quality of the adhesive bond depends on the available substrate.…”
Section: Discussionmentioning
confidence: 99%